The Discriminant Analysis of the Responses of a Sample of University Students to the Effective Intelligence Scale (Journal of Hama University, 2022)
The aim of the current research is to reveal the discriminatory ability of an effective intelligence scale to the responses of a sample of university students. The research sample consisted of (380) male and female students from the Faculties of Education and Economics at Damascus University, of whom (136 males and 244 females), and the results showed the following:- There is a statistically significant difference between the mean scores of students on the effective intelligence scale according to the gender variable, and the difference was in favor of females on all dimensions.- The distinguishing function between males and females is “dealing with the self”.- Amounted classification accuracy between the male and female groups was 76.8%.- There is a statistically significant difference between the mean scores of students on the effective intelligence scale according to the variable of academic specialization, and the difference was in favor of theoretical colleges on all dimensions.- The function of distinguishing between theoretical faculties and scientific faculties is "deliberation".- Amounted classification accuracy between the two groups of theoretical colleges and scientific colleges was 81.8%.- There are statistically significant differences between the mean scores of students on the effective intelligence scale according to the variable of the school year (first-second-third-fourth) in favor of the higher academic year on all dimensions.- The first distinguishing function between groups of students according to the variable of the school year is "deliberation", and the second distinguishing function is "optimism".- Amounted classification accuracy among groups of students according to the variable of the school year reached 52.6%.